Peri-operative acute kidney injury upon cardiac surgery time-of-day. (1st December 2018) - Ninni, Sandro; Seunes, Claire; Ortmans, Staniel; Mouton, Stéphanie; Modine, Thomas; Koussa, Mohamed; Jegou, Bruno; Edme, Jean-Louis; Staels, Bart; Montaigne, David; Coisne, Augustin
Abstract: Background: A relevant morning-afternoon variation in ischemia-reperfusion (IR) insult after cardiac surgery has been demonstrated. We speculated that the biorhythm might also impact systemic reactions involved in acute kidney injury (AKI) following cardiac surgery. We aimed at investigating incidence, determinants and prognostic impact of AKI in a large cohort of patients referred for surgical aortic valve replacement (SAVR) according to surgery time-of-day. Methods: Between 2009 and 2015, we explored consecutive patients referred to our Heart Valve Center (CHU Lille) for first SAVR. Patients undergoing morning and afternoon SAVR were matched into pairs by propensity score and followed for major events (ME) i.e. cardiovascular death, cardiac hospitalization for acute heart failure (HF) and post-operative myocardial infarction. AKI was defined using KDIGO classification. Results: In the matched population ( n = 596 patients), AKI occurred in 20% of patients. After multivariable adjustment, medical history of hypertension, pre-operative renal function impairment and cardio-pulmonary bypass duration were independent predictors of AKI onset. Post-operative AKI was significantly associated with increased occurrence of ME and specifically of cardiac hospitalization for HF ( p = 0.0035 and p = 0.0071, respectively) during the 500 days following SAVR. Finally, AKI occurrence and severity were similar between morning and afternoon groups ( p = 0.98 and p = 0.99, respectively). Conclusion: We showed that despite current high-quality patient management during and following SAVR, peri-operative AKI remains frequent, developing in 20% of patients, and clearly worsens mid-term post-operative outcomes. AKI more often develops in patients with pre-operative chronic kidney disease and long duration of cardiac surgery but is not influenced by surgery time-of-day.